Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I need to compute Fourier series for the following function: $f(x)=\frac{-\pi}{4} $ for $-\pi \leq x <0$, and $\frac{\pi}{4} $ for $ 0 \leq x \leq \pi$, and then to use it and compute $\sum_{n=1}^{\infty}\frac{1}{(2n-1)^2}$

I tried to use Parseval equality:

$$\widehat{f(n)}=\frac{1}{2\pi}\int_{-\pi}^{\pi}f(x)e^{-inx}=\frac{1}{4in}-\frac{(-1)^n}{4in}, \sum_{-\infty}^{\infty}|\widehat{f(n)}|^2=\frac{1}{2\pi}\int_{-\pi}^{\pi}|f(x)|^2.$$

$$\sum_{-\infty}^{\infty}|\frac{1}{4in}-\frac{(-1)^n}{4in}|=\frac{1}{2\pi}\int_{-\pi}^{\pi}f(x)=\frac{\pi^2}{16}.$$

Does someone see how can I compute form that the requsted sum?

Thanks!

share|improve this question
    
If I understand correctly, to denote the Fourier transform of $f$ evaluated at $n$, we write $\hat{f}(n)$, not $\widehat{f(n)}$. –  anon Feb 13 '12 at 10:31
    
I used to write it as you suggested, but I was edited to the way I used it for this question (twice), so I decided use it this time. –  Jozef Feb 13 '12 at 10:36

4 Answers 4

up vote 5 down vote accepted

Since the function is odd, we have $\widehat f(2n)=0$ for all integer $n$ and $$\widehat f(2n-1)=\frac 1{2\pi}\frac{\pi}4\left(-\int_{-\pi}^0e^{-i(2n-1)x}dx+\int_0^{\pi}e^{-i(2n-1)x}dx\right)\\\ =\frac 18\left(\frac 1{(2n-1)i}(1-(-1)^{2n-1})+\frac 1{(2n-1)i}(1-(-1)^{2n-1})\right) =\frac 1{2(2n-1)i}.$$ We have $\frac1{2\pi}\int_{-\pi}^{\pi}|f(x)|^2dx=\frac{\pi^2}{16}$ and $|\widehat f(2n-1)|^2=\frac1{4(2n-1)^2}$ so by Parseval equality $$\frac{\pi^2}{16}=\sum_{n\in\mathbb Z}|\widehat f(2n-1)|^2=\sum_{n\in\mathbb Z}\frac1{4(2n-1)^2}=\frac 14 \sum_{n\in\mathbb Z}\frac 1{(2n-1)^2}\\\ =\frac 14\sum_{n\geq 1}\frac 1{(2n-1)^2}+\frac 14\sum_{n\geq 0}\frac 1{(2n+1)^2} =\frac 12\sum_{n\geq 1}\frac 1{(2n-1)^2}. $$ and finally $$\sum_{n=1}^{+\infty}\frac 1{(2n-1)^2}=\frac{\pi^2}8.$$

share|improve this answer
    
Third row- the $n$ before the equality is probably a mistake, right? –  Jozef Feb 13 '12 at 11:26
    
Yes, I will edit it. Thanks! –  Davide Giraudo Feb 13 '12 at 11:41

Or you might want to think that

$$\eqalign{ & \omega = 1 + \frac{1}{{{2^2}}} + \frac{1}{{{3^2}}} + \frac{1}{{{4^2}}} + \cdots = \frac{{{\pi ^2}}}{6} \cr & \frac{\omega }{4} = \frac{1}{{{2^2}}} + \frac{1}{{{4^2}}} + \frac{1}{{{6^2}}} + \frac{1}{{{8^2}}} + \cdots = \frac{{{\pi ^2}}}{{24}} \cr & \omega - \frac{\omega }{4} = 1 + \frac{1}{{{3^2}}} + \frac{1}{{{5^2}}} + \frac{1}{{{7^2}}} + \cdots = \frac{{{\pi ^2}}}{6} - \frac{{{\pi ^2}}}{{24}} = \frac{{{\pi ^2}}}{8} \cr} $$

share|improve this answer

The Fourier series of $f$ is given by $$ \mathcal{F}f(x)= \sum_{k=1}^{\infty} \frac{1}{2k-1}\sin((2k-1)x), $$ which converges pointwise to $f$ except at $x=0$ (where it is zero). So on $(-\pi, 0)$, we can write $\mathcal{F}f =f$, and integrating both sides of the first equation, we get $$ -\frac{\pi^{2}}{4} = \int_{-\pi}^{0} f(x)\, \mathrm{d}x = \sum_{k=1}^{\infty} \frac{1}{2k-1}\int_{-\pi}^{0}\sin((2k-1)x) = -2\sum_{k=1}^{\infty} \frac{1}{(2k-1)^{2}} $$ which gives the result $$ \sum_{n=1}^{\infty} \frac{1}{(2n-1)^{2}} = \frac{\pi^{2}}{8} $$

share|improve this answer
    
Thank you very much :) –  Jozef Feb 13 '12 at 11:36

You want your computation of the coefficients to be in a convenient form; check that $$|\hat{f}(n)|^2=\begin{cases} (2n)^{-2} & n \text{ odd} \\ \\ 0 & n \text{ even} \end{cases} $$

The major issue I see in the work you posted is that you have an erroneous version of Parseval's:

$$ \hskip 0.3in \sum_{-\infty}^{+\infty} |\hat{f}(n)|= \int_{-\pi}^{\pi} |f(x)|dx \hskip 0.3in \color{Red}{\text{Incorrect}} $$

The correct version is with squares, which makes the computations meaningful:

$$\hskip 0.3in \sum_{-\infty}^{+\infty} |\hat{f}(n)|^2= \int_{-\pi}^{\pi} |f(x)|^2dx \hskip 0.3in \color{LimeGreen}{\text{Correct}} $$

On the left side we'll be adding $(2n)^{-2}$ over the odds twice, and the right side is $\pi^2/16$.

share|improve this answer
    
Thanks anon, I used it as it it, and wrote it in the question in the incorrect form. –  Jozef Feb 13 '12 at 11:35

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.